A espacialização do sujeito em João Gilberto Noll e Al Berto - Gustavo Cerqueira Guimaraes (2013)
This dissertation proposes a discussion about the way the self is represented in João Gilberto Nolls work (1946), a Brazilian writer, and Al Bertos, a Portuguese writer (1948-1997). It is noteworthy to highlight the emergence of these writers in the literary scene, by analysing Al Bertos book covers and Nolls protagonists voice that is expressed in his novels. Moreover, it is also important to compare and contrast these narrators spacializations around the anomalous places in the city, taking into account the notion of heterotopy. By doing this, it is remarkable that these authors make use of some strategies to make their self-portrays, which are going to be articulated with the issue of the double.